IMPLEMENTASI PEMBELAJARAN PAI BERBASIS KURIKULUM MERDEKA BELAJAR TERHADAP PENINGKATAN AKHLAK SISWA KELAS 10 JURUSAN TEKNIK BISNIS SEPEDA MOTOR DI SMK ISLAM DIPONEGORO LOSARI BREBES - Anto Santoso; Suklani Suklani; Akhmad Affandi (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This study aims to 1. Describe the implementation of Islamic Education (PAI) learning based on the Free Learning Curriculum in the Motorcycle Business Engineering Department for 10th-grade students at SMK Islam Diponegoro Losari, 2. Determine the impact of implementing PAI learning based on the Free Learning Curriculum on the Improvement of Ethics of 10th-grade students in the Motorcycle Business Engineering Department at SMK Islam Diponegoro Losari, and 3. Identify the supporting and inhibiting factors in the implementation of PAI learning based on the Free Learning Curriculum on the Improvement of Ethics of 10th-grade students in the Motorcycle Business Engineering Department at SMK Islam Diponegoro Losari. This research uses a qualitative approach with data collection techniques through interviews and observations. The main findings indicate that the implementation of PAI learning based on the Free Learning Curriculum has a positive contribution to shaping the character and morals of students. PAI teachers play a crucial role in adapting the curriculum and learning materials to be relevant to the needs and interests of students. Supporting factors include teacher training, infrastructure support, and student involvement in learning, while obstacles include a lack of resources and challenges in online implementation during the pandemic. The implications of this study underscore the importance of continually improving the quality of relevant and applicable PAI learning for students, as well as expanding support and facilities to support the implementation of the Free Learning Curriculum in vocational high schools.